Ageing impact on tribological properties of MoDTC-containing base oil. (December 2015) - De Feo, M.; Minfray, C.; De Barros Bouchet, M.I.; Thiebaut, B.; Le Mogne, Th.; Vacher, B.; Martin, J.M.
Abstract: Since last decades, there is an industry-wide need for the comprehension of how degradation affects lubricant tribological performance. The lubricating performances of MoDTC-containing base oil, fresh and aged, have been assessed using reciprocating tribometer, and XPS and TEM have been used to characterize the tribofilm formed. An induction period increasing with the degradation time was evidenced on the friction behavior when Mo-containing base oil was subjected to the degradation process and the formation of a tribofilm rich in molybdenum oxisulphides has been documented. The results found are discussed to clarify the correlation between degradation time, tribological performance and tribofilm characterizations. Highlights: MoDTC tribological behavior have been investigated as function of degradation time. The concomitance of two molybdenum oxisulphides compounds has been hypothesized. Differences on the tribofilm structure for fresh and aged oils have been observed.